2013
DOI: 10.1007/s00066-013-0371-9
|View full text |Cite
|
Sign up to set email alerts
|

Glycolysis-related gene induction and ATP reduction during fractionated irradiation

Abstract: Sensitivity-related differences in the transcriptional response of tumors to radiotherapy may be exploited in the clinic for better individualization of tumor treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…For example, ATP-dependent chromatin remodeling complexes in double-strand break (DSB) repair and poly ADP-ribose polymerase (PARP) activity are ATP dependent. [29][30][31][32][33] Thus, mitochondrial function might play an important role in cell's radio-sensitivity, and high mitochondrial respiratory capacity of CSCs might be linked with their radio-resistance through DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ATP-dependent chromatin remodeling complexes in double-strand break (DSB) repair and poly ADP-ribose polymerase (PARP) activity are ATP dependent. [29][30][31][32][33] Thus, mitochondrial function might play an important role in cell's radio-sensitivity, and high mitochondrial respiratory capacity of CSCs might be linked with their radio-resistance through DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…Coupling x-ray radiation with immunotherapy has shown promising results in preclinical and clinical studies [6,7]. Interestingly, one study has demonstrated that fractionated, but less so single, exposure to x-ray radiation leads to the suppression of glycolytic enzyme expression and decreased lactate production in the tumors [58]. The timing of immunotherapy coupled with conventional radiation therapy needs to be re-evaluated and outcomes might be improved if several fractionations preceded immunotherapy and were applied when lactate levels are at their lowest point.…”
Section: Interplay Between Radiation Therapy and Lactate Production mentioning
confidence: 99%